2018
DOI: 10.1016/j.leaqua.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Acting with the best of intentions… or not: A typology and model of impression management in leadership

Abstract: Followers accept influence when target leaders meet their perception of what it means to be a leader. Impression management (IM) is an important means of influencing these perceptions. However, extant literature on leader IM is fragmented and lacks a clear explanation of how the influence process occurs. I unify the literature in this area by creating a multidimensional typology and multi-level model of IM in leadership. I examine the multidimensional nature of IM as composed of information processing, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 180 publications
0
20
0
1
Order By: Relevance
“…While working in groups, individuals often use some impression management tactics to justify their intelligence level and their organization citizenship behaviour (OCB). Extensive research has confirmed that individuals shape their communal images based on the perceived values and choices of others (Montagliani & Giacalone, 1998;Goveetal, 1980;Giacalone & Rosenfeld, 2013;Bolino et al, 2016;Kacmer et al 2016;Brouer et al 2016;Peck & Hogue, 2018;Brouer et al, 2016). In this manner, impression management is the method by which the individual manage the impressions of other individuals, and this process plays an critical role in determining the interpersonal behaviour (Leary & Kowalski, 1990).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…While working in groups, individuals often use some impression management tactics to justify their intelligence level and their organization citizenship behaviour (OCB). Extensive research has confirmed that individuals shape their communal images based on the perceived values and choices of others (Montagliani & Giacalone, 1998;Goveetal, 1980;Giacalone & Rosenfeld, 2013;Bolino et al, 2016;Kacmer et al 2016;Brouer et al 2016;Peck & Hogue, 2018;Brouer et al, 2016). In this manner, impression management is the method by which the individual manage the impressions of other individuals, and this process plays an critical role in determining the interpersonal behaviour (Leary & Kowalski, 1990).…”
mentioning
confidence: 95%
“…The individuals are pleased to show their positive image to others to have a good feeling about them (Nasr Esfahani, 2002;Giacalone & Rosenfeld, 2013). Nowadays, individuals, tend to use some impression techniques to impress others to get any long-term benefits (Schlenkar, 1980;Brouer et al, 2016;Peck & Hogue, 2018). The organizational impression management techniques are followed by the employees to influence the employer's behaviour, attitudes, and belief (Yu, 2019) Goffman (1959) developed the term 'impression management' and defined it as a purposeful action that people follow to build optimistic and positive distinctiveness and social image (Zerbe & Paulhus, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, employees may also practice impression management, which is a series of behaviors performed in order to be viewed more favorably by others (Bolino et al, 2016). Examples include adjusting one’s leadership style to gain influence (Proell, Sauer, & Rodgers, 2016), taking credit for others' work (Peck & Hogue, 2018), and altering job performance behavior while searching for jobs externally (Ahn & Ok, 2019). As individuals who use impression management strategies tend to be agreeable or conform to supervisors (Bolino, Kacmar, Turnley, & Gilstrap, 2008), it is conceivable they might not provide true scores on questionnaires related to their current jobs.…”
Section: Introductionmentioning
confidence: 99%
“…These instances are relatively ignored in the scientific body of research on charisma. Specifically, our goal is to test to what extent the immediate impression of the speaker—a mean to impact one’s perception (Peck & Hogue, 2018)—is updated after noticing that the message and the delivery are misaligned. We claim that the delivery is processed rapidly whereas the message is processed slowly; furthermore, delivery is granted dominance when perceiving charisma.…”
Section: Introductionmentioning
confidence: 99%